Understanding the potential of market and brand orientations: An empirical investigation of the mediating role of brand equity on business performance - Jha, Rohan Kumar; Sarabhai, Samar (International Journal of Management and Sustainability, 2024)
Brand Orientation and Market Orientation have been demonstrated to exert a significant impact on brand equity. Moreover, brand equity serves as a crucial link connecting these orientations to company performance. However, the existing literature presents a substantial gap in understanding this relationship, particularly within the context of India. To address this gap, this study proposes an innovative framework for examining the interplay between brand orientation, market orientation, business performance, and brand equity. A survey was done in northern India using a causal study design to determine cause-and-effect correlations among the components. The participants were asked to respond to an English-language questionnaire. The outcomes of the structural equation modeling (SEM) analysis support all of the proposed hypotheses. The findings of this study carry significant implications for businesses aiming to optimize their brand and market orientations while capitalizing on their brand equity to enhance their overall performance. This research offers fresh insights for businesses operating in diverse cultural and economic contexts through its innovative methodology and empirical evidence. Businesses can enhance their brand and reputation, launch tailored offerings, and gain a competitive advantage through market and brand orientation. The framework developed in this study can be adapted to other emerging economies or even larger organizations. For both businesses and academics, this research serves as a valuable resource, providing a deeper comprehension of the intricate relationship between brand orientation, market orientation, company performance, and brand equity in India and beyond.